Kestabilan Propoxur dalam Berbagai Solven Sebagai Upaya Pengurangan Resiko Keselamatan dan Lingkungan dengan Pendekatan Komputasi - BADRA SANDITYA RATTYANANDA; CAHYONO DANANG PRASETYO; HASAN HARIRI (UIN Sunan Gunung Djati Bandung, 2022)
Propoxur was an active ingredient of pesticide that was commonly used as an insecticide. In Indonesia, Propoxur was produced by PT. Inti Everspring Indonesia by reacting MIC with ortho-Isopropoxy phenol with xylene solvent. The use of xylene as a solvent can lead to bad consequences if not handled properly, ranging from harm to the body, flammable and can poison the environment. Therefore, it was necessary to conduct a study to replace xylene with other solvents that were less harmful and environmentally friendly. The research was conducted by simulating propoxur with ORCA software using the PBE method and the basis set 6-31G. After optimum structure obtained, the electronic energy in various solvents using implicite approach with the SMD method compared. The electronic energy obtained in the gas phase was -707.60003 eh. In polar solvents, the energy obtained were -707.61585 eh in water and -707.61548 eh in DMSO. In non-polar solvents, the energy obtained were -707.61512 eh for xylene, -707.61563 eh in Toluene, -707.61756 eh in Iodobenzen, and -707.61970 eh in Ortho-Dichlorobenzene (ODCB). For the solvent in the form of ionic liquid, it was found that -707.61602 eh for [EMIM][TfO] and -707.61392 eh for [BMIM][BF4]. From the simulation, it was found that xylene as propoxur solvent is possible to be replaced with benzene-derived solvents, namely Iodobenzene and ODCB. The ionic liquids usage for solvent was very possible to be developed in the future because it was more environmentally friendly even though the price is still very high. In the future, it was necessary to carry out further energetic studies to determine whether the change in solvency affects the activation energy and laboratory tests to follow up on these computational result